The hot spots and global trends of prevention and treatment in postoperative delirium (POD) from 2004 to 2023: A bibliometric analysis - Changshuo Jiang; Zijun Tian; Ming Jiang; Chenyang Xu; Mingjie Mao; Shanwu Feng; Hongmei Yuan (Surgery Open Science)
Background: Postoperative delirium (POD) is an acute postoperative syndrome of the central nervous system that seriously affects the prognosis of patients. Many vital advances have been made in the study of the management of POD. We conducted a bibliometric analysis of research on the prevention and treatment of POD over the past 20 years to consolidate current research focal points and emerging trends in this domain. Methods: We searched the Web of Science Core Collection database for literature published between 2004 and 2023. VOSviewer, CiteSpace, Microsoft Excel, Scimago Graphica, and the R tool “bibliometrix” were used to analyze and visualize annual publications, countries, organizations, journals, authors, keywords, and references. Results: A total of 1848 eligible publications were identified, with a general uptrend observed in both annual publications and citations. The USA was the most profitable country, ranking first in total publications. The most active institution was Harvard Medical School. Inouye, Sharon K was the most prolific scholar due to her numerous publications and citations. According to the co-occurrence network, the strongest citation bursts and co-cited references analysis fresh hot topics included “dexmedetomidine,” “neuroinflammation,” “haloperidol prophylaxis,” and “guideline.” Conclusions: Research on prevention and treatment of POD is gaining significant momentum worldwide. Current hot spots include early perioperative prevention strategies and integrated multi-method treatments. Effective drugs for it is one of the directions in the future. The management of pediatric patients with POD has caused concern in recent years. This bibliometric analysis is poised to guide future research trajectories in this field.